NATION-BUILDING AND CULTURAL POLICY IN KAZAKHSTAN - Melich, Jiri; Adibayeva, Aigul (European Scientific Journal, ESJ, 2014)
Kazakhstan, the last emerging independent state from the former Soviet Union, inherited multiple challenges of having to build a new state and nation, while engaged in the painful economic and political transformation. Since independence was declared in 1991, diversity and tolerance have been officially at the heart of Kazakhstan’s national identity. Nevertheless, building a single nation in the country of two large ethnic groups (Russians and Kazakhs), with the reversed proportion of the language proficiency – as there are more ethnic Kazakhs but more Russian-speakers in the country – has been an ambivalent and controversial process. Constructing a nation in a primordial sense in this multi-ethnic country might well prove to be a mission impossible. Another option is promotion of the idea of a civic nation based on carefully drafted and consciously adapted multicultural policies. The existence, implementation, and success of such policies are contingent on several factors, including historical, demographic, and social ones. Some are linked to expedient political and economic strategies, however, and their further development would entail democratization of the political system in Kazakhstan. It seems that in Kazakhstan, inter-ethnic tensions have been alleviated by the fact that two major ethnic groups have not been, by and large, in direct confrontation and are balancing each other in the managed tradeoffs. So far, the dynamically developing society might be able to accommodate the interests of major ethnic groups but all the proposed solutions are inconclusive. The focus of this paper is on the bi-lingual and multicultural constellation and cultural and language policy pathways in Kazakhstan, as analyzed through the lenses of several models available in the respective literature on post-communist nation-building. The paper’s the methodology explores systematic historical and cultural interpretations and comparative intercultural-institutional analysis.